Factors Affecting Application Launch Time with Android OS - Noori, Khalid Sabah; Fahad, Assmaa A. (Iraqi Journal of Science, 2020)
Android OS is developing very fast, and because of being an open source OS, it is vulnerable to many problems that are manifested to users directly or indirectly. Poor application launch time is one of these problems. In this paper, a set of sixteen experiments is established to distinguish the factors that have the most evident effects on application launch time in Android mobiles. These factors are application, launch and kill, events, and storage. Mann Kendall (MK) test, one way analysis of variance (ANOVA), and Design of Experiment (DOE) are used to prove the influence of factors statistically. As a result of the experiments, the application factor, especially the third party applications level, has the most prominent effects on application launch time, followed by launch and Kill and events, while storage had the least influence.